Study of the influence of the parameters of preparation of polymeric solutions obtaining nanofibers by electrospinning - Luiz Fernando Pimenta Gonçalves; Ariandy Botezini; Carlos Omizollo Wittcinski; William Roberto da Silva Santos; Erika Peterson Gonçalves (The Journal of Engineering and Exact Sciences)
The technique of electrospinning polymeric nanofibers has been emerging in the academic environment due to its well-parias and low operational, but the production of these nanofibers finds challenges regarding homogeneity and reproduction of obtained results. As properties of polymeric solutions are important for the determination of electrospinning parameters, such as the applied electrical voltage and injection rate. Seeking rheological behavior of polymeric solutions; which may be affected by the concentration of the polymeric solution and the preparation temperature of these solutions. This way this work studied the effect of the production temperature of polyacrylonitrile and methyl acrylate copolymer solutions and related them to the nanofibers produced at the same injection rates and electrical stresses. It was observed the inversely proportional behavior between the temperature of preparation of the solutions and the viscosity of the solutions at room temperature, which reflects in the integrity and homogeneity of the fibers formed, with the formation of pearls in the nanofibers produced to more viscous solutions.